Kontestasi Regulasi Perkawinan dan Fikih Munakahat dalam Masalah Nikah Siri di Kota Sungai Penuh (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2024)
This article discusses the conflicting understanding of marriage regulations and munakahat fiqh on the issue of nikah siri. This conflict has occurred in Sungai Penuh City to date. This article discusses three points. First, about the understanding of religious leaders in Sungai Penuh about the relationship between fikih munakahat and the Marriage Regulations. Second, about the understanding of the Marriage Registration Officer in Sungai Penuh about the relationship between fikih munakahat and the Marriage Regulations. Third, about the motives and patterns of contestation of fikih munakahat with the Marriage Law in Sungai Penuh and Sungai Penuh. This study shows that religious leaders in Sungai Penuh City still conflict between fikih munakahat, which does not require marriage registration, and marriage regulations that require marriage registration. Some are of the view that marriage registration has no substantial role except as an administrative necessity. Therefore, marriage registration is often ignored as most people ignore other administrative processes, so siri marriages are still rampant.